Perceptions of Wind Turbine Noise and Self-Reported Health in Suburban Residential Areas - Qu, Fei; Tsuchiya, Aki (Frontiers in Psychology, 2021)
Wind turbines play an important role in the worldwide mission of producing renewable energy. The development towards integrating large-scale wind turbines in the urban environment has raised concerns over the noise impacts on urban residents. While most existing studies on wind turbine noise have focused on rural settings, this paper investigates the relationship between wind turbine noise, people’s noise perception and self-reported health, controlling for background characteristics of the residents in urbanized areas. Questionnaire surveys were carried out around three suburban wind farms in the UK with 359 respondents. A-weighted sound pressure levels of wind turbine noise were predicted using noise mapping, for the most exposed façade of each respondent’s dwelling. Dose-response relationship was found between wind turbine noise and annoyance, moderated by age and degree of education. Wind turbine noise was associated with some aspects of self-reported health, including raised health concerns, having headache, nausea, and ear discomfort, but was not related to sleep disturbance directly. Noise sensitivity, attitudes to wind energy, and visibility of the wind turbines were found to significantly influence self-reported health. By employing a second variant of the questionnaire with the research aim masked, this study also addressed the focusing effects induced by questionnaire design. The significant differences in reported adverse health between questionnaire variants implied focusing bias among the sample who knew the research purpose. This elicited a methodological finding which should be noted in future research.